The Multielectrodes Oscillation System Studied by Irreversible Thermodynamics - Eko Suhartono; Djaka Sasmita; RHA. Sahirul Alim (Universitas Gadjah Mada, 2001)
Oscillation process that occurs in a system may be formed from non linear dynamic phenomena that far from equilibrium. Mechanism of oscillation in a chemical reaction system such as Belousov-Zhabotinski (B-Z) reaction is quite complex. For that reason, in order the irreversible thermodynamics that far from equilibrium can be more easily understood, the generation of oscillation in a system is tried to be investigated in this study. In this case, the author attempts to come up at the oscillation process coming from the potential difference between the couple of Pb and PbO2 electrodes which are parallel arranged to from eight channels in the solution of sulfuric acid with certain concentrations. The measurements of potential difference from PbllPbO2 electrode, i.e., from the eight channels all together, were done by the use of an interface connected to a computer and it worked with time interval of one second for the time duration of 5 hours. The data were then automatically recorded. Non periodic waves which were resulted from all channels have wave forms which are triangular and square. Oscillation process occurred in each channel of a couple of PbIIPbO2 electrodes can be compared with the process of spreading of action potentials that occur in nerve cells.